1997
DOI: 10.1159/000119324
|View full text |Cite
|
Sign up to set email alerts
|

GABA Uptake Sites in Frontal Cortex from Suicide Victims and in Aging

Abstract: The binding of [3H]nipecotic acid to GABA uptake sites was studied in post mortem human frontal cortex from 17 suicide victims and 21 controls without known neurological or psychiatric disorder. The suicide victims were subclassified according to the use of violent or non-violent methods and to the presence or absence of a known history of a depressive disorder. No difference was found between the suicide victims and the controls with regard to [3H]nipecotic acid binding to GABA uptake si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 16 publications
1
7
1
1
Order By: Relevance
“…Despite the pharmacological evidence consistent with a role for GABA in depression (Krystal et al, 2002;Brambilla et al, 2003), limited data are available concerning GABA changes in postmortem brain. Although Cheetham et al (1988) reported elevated GABA A receptors, others reported that neither GABA levels nor GABA B binding was altered in depressed suicides (Cross et al, 1990;Arranz et al, 1992;Sundman et al, 1997). The present findings indicated that GABA A subunit mRNA expression, particularly with respect to the ␣1, ␣3, ␣4, and ␦ receptor subunits, was lower in depressed suicides than in controls, and that these effects were regionally specific, being evident in the frontopolar cortex, but absent in both the dorsomedial and ventrolateral prefrontal cortex.…”
Section: Discussioncontrasting
confidence: 53%
“…Despite the pharmacological evidence consistent with a role for GABA in depression (Krystal et al, 2002;Brambilla et al, 2003), limited data are available concerning GABA changes in postmortem brain. Although Cheetham et al (1988) reported elevated GABA A receptors, others reported that neither GABA levels nor GABA B binding was altered in depressed suicides (Cross et al, 1990;Arranz et al, 1992;Sundman et al, 1997). The present findings indicated that GABA A subunit mRNA expression, particularly with respect to the ␣1, ␣3, ␣4, and ␦ receptor subunits, was lower in depressed suicides than in controls, and that these effects were regionally specific, being evident in the frontopolar cortex, but absent in both the dorsomedial and ventrolateral prefrontal cortex.…”
Section: Discussioncontrasting
confidence: 53%
“…140 GABA A receptor binding sites have been found to be abnormally increased in frontal cortex of depressed suicide victims, 141 suggesting lowered GABAergic activity in those patients. However, no significant differences between suicide victims and nonpsychiatric controls for GABA A and GABA B receptor binding sites, [142][143][144][145] GAD activity, 141 and GABA concentration 146 have been found in several brain areas. Recently, support for abnormally decreased GABAergic neurotransmission in anterior cingulate, prefrontal cortex, and hippocampus in bipolar, but not unipolar disorder patients has been reported by several postmortem studies, as shown by decreased expression of GAD 65 and GAD 67 and decreased density of GABAergic neurons.…”
Section: 103mentioning
confidence: 87%
“…This reaction is sensitive to tricyclic antidepressants and electroconvulsive shock therapy (ECST), but not to anxiolytic or major GABA plasma levels kin 40% of depressed, manic, and euthymic mood disorder patients 98,[116][117][118][119][120] 2 in depressed patients 132 GABA enzyme activities kplatelet GABA-T and plasma GAD activities in unipolar and bipolar patients 127,128 Post-mortem studies kGAD activity 130 and mGABA A receptors 141 in the brain of depressed patients k GABA cortical levels with m depression severity in mood disorder patients 151 kexpression of GAD 65 and GAD 67 in prefrontal cortex 148 [141][142][143][144][145][146] Neuroimaging studies kGABA A receptors in the sensory motor cortex of mood disorder patients with akinetic catatonia 152 kGABA occipital cortex levels in depressed patients 153 Neuroendocrine studies (GH response to baclofen ) k in depressed patients 163,164 m in manic patients 161 2 in depressed patients, 162,165,166 Genetic studies Bipolar disorder: association with GABA A receptor a5 (GABRA5) 178 and a3 subunits (GABRA3) 180 possible linkage of GABRA5 and GABA A receptor b1 subunit (GABRB1) loci 181 no association with GABRA1, 179,181,186,188 70,71 Reduced GABA levels in rat nucleus accumbens, brain stem, and cortex have been reported after a session of forced swimming test. 72 Also, muscimol, a GABA agonist, reduced the immobility,...…”
Section: Gaba and The Pathophysiology Of Mood Disordersmentioning
confidence: 99%
“…There are several studies in the literature performed with post mortem human brain of suicide victims. In one study, no differences in [ 3 H]nipecotic acid binding sites was reported in terms of method of suicide, presence of depressive symptom or in comparison with post-mortem human frontal cortex with regard to aging [40]. Suicide, without doubt, may be considered one of the most stressful situations occurring in humans.…”
Section: Discussionmentioning
confidence: 99%